Exploring writing and play in the early years - Hall, Nigel, 1947- (David Fulton, 2003)
This new edition shows how play and literacy can combine to help young children develop a more complete understanding of writing, as well as literacy more generally. Early years practitioners will find that this book helps them to focus on the development of literacy knowledge and skills.